Character Education In Psycholinguistics In Arabic Language Learning For Children/ Pendidikan Karakter Pada Psikolinguistik Dalam Pembelajaran Bahasa Arab Untuk Anak - Fauzi, Layyina Khoirun Nisa; Nurjannah, Nurjannah (Bumi Lingua Edu Center, 2024)
Psycholinguistics studies the psychological factors discussed, namely character education related to the psychology of students. This study aims to describe character education in Psycholinguistics, factors that influence the implementation of the character approach, psycholinguistics in Arabic language learning communication interactions, and Arabic language communication learning media for children. The research method uses a qualitative descriptive design. Data were collected through literature reviews using library research techniques, namely by understanding and reviewing theories presented in various works relevant to the study. Research results: Character education in Psycholinguistics is considered necessary for school students. Psycholinguistics and character education go hand in hand because character education facilitates the application of students' psycholinguistic concepts in real-world situations. Factors that influence the implementation of the character approach are divided into two: internal factors, such as environmental elements at school, and external factors, such as elements that support and help children understand lessons about character education. Therefore, it is known that internal and external factors of the school influence how the character approach is applied in the classroom. Psycholinguistics in Arabic language learning communication interaction Psycholinguistics carefully considers the language processes that occur in the brain during language production by the speaker and during language perception by the listener, such as maharah Istima (listening skills) including determination and communication, maharah kalam (communicative skills) including social and democratic concerns, maharah qiro'ah (reading skills) including curiosity and a love of reading, and maharah kitabah (writing skills) including independence and recognition of achievement. Arabic language communication learning media for children include visual media (bashariyah/visual) for example overhead projectors (OHP), slides, film strips, silent films, and loop films, and audio or listening media (sam'iyah) for example language laboratories, tape recorders, and radios.